Ketidakpedulian Terdidik Di Komunitas Pesisir: Analisis Melalui Perspektif Akuntansi Perilaku - Aptasari, Fety Widianti; Falah, Muhammad Helmi; Budiman, Budiman; Putri, Baiq Krisnina Maharani (Politeknik Negeri Ambon, 2025)
Indonesia's coastal communities have great potential in managing marine resources but are still trapped in various challenges, especially in terms of environmental awareness. Poverty, low education levels, and cognitive biases such as status quo bias make them increasingly marginalized from environmental policies. Lack of trust in institutions and the dominance of individualistic values further exacerbate the disengagement of coastal communities towards collective action. In addition, the high use of single-use plastics is triggered by economic factors and the lack of incentives to switch to more environmentally friendly behavior. This study uses a behavioral accounting approach and Systematic Literature Review (SLR) to understand how economic and psychological factors shape the behavior of coastal communities toward environmental issues. The results of the analysis show that without incentive-based policies and more systematic education, behavior change is difficult to occur. Therefore, a co-management approach that actively involves communities in natural resource management is needed, as well as incentive-based strategies that can foster a sense of ownership of environmental policies. With the right interventions, inclusive and sustainable coastal development can be achieved, bringing ecological benefits and community welfare together.